Overview of literature on RMC and applications to Tanzania - Karline Wilson-Mitchell; Lucia Eustace; Jamie Robinson; Aloisia Shemdoe; Stephano Simba (BMC, 2018)
Abstract Respectful maternity care research in Tanzania continues to increase. This is an overview of the literature summarizing research based on the domains which comprise this quality of care indicator, ranging from exploratory and descriptive to quantitative measurements of birth perinatal outcomes when respectful interventions are made. The domains of respectful care are reflected in the seven Universal Rights of Childbearing Women but go further to implicate facility administrators and policy makers to provide supportive infrastructure to allay disrespect and abuse. The research methodologies continue to be problematic and several ethical cautions restrict how much control is possible. Similarly, the barriers to collecting accurate accounts in qualitative studies of disrespect require astute interviewing and observation techniques. The participatory community-based and the critical sociology and human rights frameworks appear to provide a good basis for both researcher and participants to identify problems and determine possible solutions to the multiple factors that contribute to disrespect and abuse. The work-life conditions of midwives in the Global South are plagued with poor infrastructure and significantly low resources which deters respectful care while decreasing retention of workers. Researchers and policy-makers have addressed disrespectful care by building human resource capacity, by strengthening professional organizations and by educating midwives in low-resource countries. Furthermore, researchers encourage midwives not only to acquire attitudinal change and to adopt respectful maternity care skills, but also to emerge as leaders and change agents. Safe methods for conducting care while addressing low resources, skilled management of conflict and creative innovations to engage the community are all interventions that are being considered for quality improvement research. Tanzania is poised to evaluate the outcomes of education workshops that address all seven domains of respectful care.